Herbs and Spices Modulate Gut Microbiota Composition: A Randomized, Crossover, Controlled-Feeding Study. (7th June 2021) - Petersen, Kristina; Kris-Etherton, Penny; Anderson, Samantha; See, Jeremy Chen; Rogers, Connie; Proctor, David; West, Sheila; Lamendella, Regina
Abstract: Objectives: The effect of culinary doses of herbs and spices, consumed as part of a well-defined dietary pattern, on gut microbiota composition has not been previously studied. The aim of this study was to examine gut microbial composition following an average American diet (carbohydrate: 50% kcal; protein: 17%; total fat: 33%; saturated fat: 11%; sodium: 3000 mg/d) containing herbs and spices at 0.5 (Low Spice Diet; LSD), 3.3 (Moderate Spice Diet; MSD) and 6.6 (High Spice Diet; HSD) g/day/2100 kcal in adults at-risk for cardiovascular disease (CVD). Methods: Fifty-four adults (57% female; 45 ± 11 years, BMI 29.8 ± 2.9 kg/m 2 ; waist circumference 102.8 ± 7.1 cm) were included in this three-period, randomized, crossover, controlled-feeding study. Each diet was provided for 4-weeks with a minimum 2-week wash-out period. At baseline and the end of each diet period subjects provided a fecal sample for 16S rRNA gene sequencing. QIIME2 was used for data filtration, sequence clustering, taxonomy assignment and statistical analysis. Linear discriminant analysis Effect Size (LEfSe) analyses were used to determine enriched biomarker taxa following each diet. Results: No between-diet differences in alpha diversity were observed based on Faith's Phylogenetic Diversity, Observed Operational Taxonomic Units (OTUs), and Pielou's Evenness (Kruskal-Walllis, P > 0.05). Principal coordinate analysis showed beta-diversity following the HSD significantly differed from baseline (PERMANOVA, P = 0.030). LEfSe pairwise analyses identified multiple taxa that were differentially abundant following the spice-containing diets vs. baseline. Compared to baseline, 34 taxa were enriched with the HSD, 22 taxa were enriched with the MSD and 20 taxa were enriched with the LSD. Members of the taxa enriched with the HSD are known short-chain fatty acid producers ( Faecalibacterium and Butyricimonas ). Conclusions: The addition of herbs and spices at 0.5, 3.3, and 6.6 g/day/2100 kcal to an average American diet altered gut microbiota composition, and resulted in enrichment of short-chain fatty acid producers, after 4-weeks in adults at elevated risk for CVD. Funding Sources: McCormick Science Institute; NCATS NIH (1UL1TR002014–01); Grant from the Howard Hughes Medical Institute through the Precollege and Undergraduate Science Education Program to Juniata College supported the computational research.